Unraveling the Role of the Tumor Extracellular Matrix to Inform Nanoparticle Design for Nanomedicine - Marco Cassani; Soraia Fernandes; Stefania Pagliari; Francesca Cavalieri; Frank Caruso; Giancarlo Forte (Advanced Science)
Abstract The extracellular matrix (ECM)—and its mechanobiology—regulates key cellular functions that drive tumor growth and development. Accordingly, mechanotherapy is emerging as an effective approach to treat fibrotic diseases such as cancer. Through restoring the ECM to healthy‐like conditions, this treatment aims to improve tissue perfusion, facilitating the delivery of chemotherapies. In particular, the manipulation of ECM is gaining interest as a valuable strategy for developing innovative treatments based on nanoparticles (NPs). However, further progress is required; for instance, it is known that the presence of a dense ECM, which hampers the penetration of NPs, primarily impacts the efficacy of nanomedicines. Furthermore, most 2D in vitro studies fail to recapitulate the physiological deposition of matrix components. To address these issues, a comprehensive understanding of the interactions between the ECM and NPs is needed. This review focuses on the main features of the ECM and its complex interplay with NPs. Recent advances in mechanotherapy are discussed and insights are offered into how its combination with nanomedicine can help improve nanomaterials design and advance their clinical translation.